LEO-CalSat for the calibration of W-band ground-based CMB polarization experiments - Casas, Francisco Javier; Martinez-Gonzalez, Enrique; Cubas, Javier; Pascual-Cisneros, Guillermo; Sánchez-Ramos, Irene; Castelló, Laura; Vielva, Patricio; Barreiro, Belén (Frontiers in Astronomy and Space Sciences, 2026)
IntroductionThe current generation of ground- and space-based Cosmic Microwave Background (CMB) telescopes demands highly precise calibration procedures. However, commonly used celestial polarized sources, such as Tau-A, are not characterized with the level of accuracy required for these experiments. This limitation has motivated several initiatives aimed at developing well-characterized artificial signal sources onboard aerial platforms, enabling observations from the telescopes’ far-field. MethodsIn this context, we propose the deployment of a polarized signal source operating in the W-band (75–110 GHz) onboard a dedicated calibration satellite, referred to as CalSat, in Low Earth Orbit (LEO). This platform would facilitate the calibration of ground-based CMB polarization experiments with significantly improved accuracy compared to traditional celestial sources. During calibration operations, the LEO-based CalSat would emit purely polarized microwave radiation from the far field, directed toward the CMB telescopes.ResultsMoreover, LEO-CalSat could also contribute to the calibration of space-based missions operating at the second Lagrange point (L2) by enhancing the characterization of polarized celestial sources, while simultaneously increasing the Technology Readiness Level (TRL) for the future deployment of a calibration satellite at L2. Various launch and satellite platform options are currently under consideration, including Spectrum shuttles and/or MIURA launchers, as well as micro-satellites such as UPMSat-4 and CubeSats.DiscussionThe anticipated launch date for the LEO-CalSat mission, which targets an orbital altitude of at least 400 km, is initially scheduled for the first half of 2026. Within our collaboration, the Universidad Politécnica de Madrid (UPM) team is responsible for the satellite’s design and development, while the IFCA/IPMU team is tasked with the development of the payload signal source.